Bridging barriers on risk management and preparedness through participatory designing of a visual communication tool the case of Higaonon indigenous community of Barangay Caburacanan, Bukidnon - Lumilang, Krizzha Mae R. (2023)
This research production thesis initially explored the application of a radiobased infomercial in delivering risk preparedness and management information to the Higaonon community of Barangay Caburacana, Malaybalay City. However, the course of this study changed which led to the creation of a visual communication tool specifically a poster risk preparedness and management. The researcher anchored the study to Cappricio?s Elaboration Likelihood Model. The researcher has changed the theoretical framework of the study to Development Communication Theory (1972) established by Dr. Nora Quebral as it is applicable the underlying principle and participatory nature of the study. The researcher conducted a two-part focused group discussion with members of the Higaonon Community in Brgy. Caburacanan to: 1. Extract their cultural concepts pertaining to environmental hazard, specifically landslides and 2. Do a workshop integrating their conceptualization of hazard to the design of a poster. From the focused-group discussion, the data were analyzed and organized by the researcher and the participants to have a detailed basis for the messages that needed to be curated and conveyed to the target audience. Design elements of the visual communication tool were anchored on the assimilated Higaonon culture. This study produced a localized informational visual communication tool intended to communicate key messages landslide risk preparedness and management tailored to the cultural views and information needs of the target audience.